2017
DOI: 10.1371/journal.pone.0170031
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the JAK-STAT Signaling Pathway after In Vitro Stimulation with IFNß in Multiple Sclerosis Patients According to the Therapeutic Response to IFNß

Abstract: Interferon beta (IFNß) is a common treatment used for multiple sclerosis (MS) which acts through the activation of the JAK-STAT pathway. However, this therapy is not always effective and currently there are no reliable biomarkers to predict therapeutic response. We postulate that the heterogeneity in the response to IFNß therapy could be related to differential activation patterns of the JAK-STAT signaling pathway. Our aim was to evaluate the basal levels and the short term activation of this pathway after IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The anti‐IFNAR monoclonal antibody might compete with IFNα2 for binding to IFNAR‐1, as is true of other anti–IFNAR‐1 monoclonal antibodies . Alternatively, since type I IFN binding induces IFNAR‐1 internalization , receptor expression could be modulated by endogenous type I IFN (SLE patients) or exogenous IFNα2b (in vitro). The latter explanation may be more likely, since a 1‐hour preincubation with IFNα2b prior to staining with anti‐IFNAR antibodies did not cause a dose‐dependent reduction in IFNAR staining (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The anti‐IFNAR monoclonal antibody might compete with IFNα2 for binding to IFNAR‐1, as is true of other anti–IFNAR‐1 monoclonal antibodies . Alternatively, since type I IFN binding induces IFNAR‐1 internalization , receptor expression could be modulated by endogenous type I IFN (SLE patients) or exogenous IFNα2b (in vitro). The latter explanation may be more likely, since a 1‐hour preincubation with IFNα2b prior to staining with anti‐IFNAR antibodies did not cause a dose‐dependent reduction in IFNAR staining (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…90 In addition, a positive correlation between serum IFNα and various disease parameters has also been established. 94 Several studies have demonstrated that IFNβ induces endocytosis and degradation of IFNAR1 to regulate the cell signaling. The relative lack of detectable IFNβ in serum is consistent with its much higher affinity for cell-surface bound IFNAR1 and IFNAR2, as well as a lower absolute abundance.…”
Section: Ifnα Vs Ifnβmentioning
confidence: 99%
“…92 Functionally, the higher affinity of IFNβ for IFNAR1 and IFNAR2 increases the efficiency of ternary complex formation and stability, especially at low receptor surface concentrations. 94 94 Several studies have demonstrated that IFNβ induces endocytosis and degradation of IFNAR1 to regulate the cell signaling.…”
Section: Ifnα Vs Ifnβmentioning
confidence: 99%
See 2 more Smart Citations